Application of social cognitive theory and Islamic theory of consumer behavior in accessing Muslim behavior toward halal nutraceuticals - Shamsudin, Siti Nurunnajwa; Abu Bakar, Elistina; Osman, Syuhaily; Mohd Dali, Nuradli Ridzwan Shah (Emerald Publishing, 2024)
Purpose: This study aims to explore the factors influencing Muslim behavior toward halal nutraceutical products in Malaysia. Design/methodology/approach: This study used a quantitative survey approach to 400 Muslim respondents in Malaysia who have experience in consuming or purchasing nutraceutical products. The sampling technique used was multistage stratified sampling, and the data was analyzed using structural equation modeling. Findings: This study revealed that perceived safety is the most influential factor contributing to Muslims’ behavior toward halal nutraceutical products in Malaysia, followed by Islamic values, trust, religiosity, maqasid al-Shariah and halal literacy. Research limitations/implications: This study has only focused on halal nutraceutical products from the perspective of Muslim consumers in Malaysia. Originality/value: This study contributes to understanding the factors that influence Muslim consumers’ behavior toward halal nutraceutical products by adopting the Social Cognitive Theory and Islamic Theory of Consumer Behavior.